ChemInform Abstract: Synthesis and Characterization of Fluorinated Bisphenols and Tetraphenols via a Simple One‐Pot Reaction. Issue 43 (7th October 2013) - Tao, Liming; Yang, Haixia; Liu, Jingang; Fan, Lin; Yang, Shiyong
Abstract TfOH‐catalyzed condensation of catechol (I) with trifluoroacetophenones (II) affords previously unreported phenolic polyphenylalkane derivatives (III), while similar reactions of resorcinol and hydroquinone furnish the corresponding novel hydroxy‐substituted xanthene derivatives (V) and (VII), respectively.